Perancangan Website Politeknik Pancasakti Global dengan mengintegrasi Sistem Pendaftaran Mahasiswa Baru Menggunakan Stack Modern Next.js dan Golang - Dwiki Mardiyanto; Rudi Heryanto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The rapid advancement of information technology encourages higher education institutions to transform in providing information services that are effective and easily accessible. One of the efforts that can be made is by developing a website-based platform capable of reaching not only students, lecturers, and administrative staff, but also the wider community. Thus, the delivery of both academic and non-academic information can be carried out more quickly, accurately, and efficiently.This study aims to design and develop a dynamic and interactive campus website as a means of improving the quality of digital information services while strengthening the institution’s image in the modern era. In its development, the waterfall method is applied.The website is built using the Go (Golang) programming language on the backend, supported by a MySQL database, and designed with a responsive and user-friendly interface. This enables content management to be more structured, flexible, and easily updated in real time according to needs.The results of this study indicate that the developed system is capable of improving efficiency in information management, enhancing the quality of services provided to users, and delivering a more optimal user experience. In addition, the website supports digital promotion strategies and facilitates the online student admission process, thereby creating information services that are more transparent, professional, and aligned with current technological developments..